A ANALISIS LAPORAN KEUANGAN TERHADAP PERGERAKAN HARGA SAHAM PADA PERUSAHAAN SUB SEKTOR PERBANKAN SYARIAH DALAM BURSA EFEK INDONESIA 2020-2021. - Muhammad Helmi Anshori (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2024)
The investment world was faced with the covid-19 pandemic in 2019. Corona Virus Disease 19 (COVID-19) which began to attract world attention after January 20, 2020. All banks are experiencing turmoil in their intermediary function which tends to decline both from financing and raising funds. This certainly affects the net profit earned by Islamic banking companies which comes from the unsuccessfulness of a bank in managing its assets and capital. Seeing this anxiety, the author conducted research aimed at examining the effect of return on assets, return on equity, and earning per share as independent variables on the share price of Islamic banking companies listed on the Indonesia Stock Exchange in 2020-2021. In this case, the author uses Signaling and Agency theories which aim to provide signals to shareholders or investors regarding company management in seeing the company's future prospects, and explain the separation between management functions and ownership functions in a company. The sample collection uses purposive sampling and then analyzed using panel data regression analysis to see the influence of the independent variables on the dependent variable either jointly or individually. The results of the regression analysis of the t-test return on asset, return on equity, and earning per share have a significant effect on stock prices. For the F test, the Prob. value of F is 0.0000, which means that return on asset, return on equity, and earning per share, simultaneously affects stock price. The coefficient of determination R2 is 0.840014 which indicates that 84.0014% of the stock price can be explained by the return on asset, return on equity, and earning per share.